GROWTH PROMOTING POTENTIAL OF GARLIC, GINGER, TURMERIC AND FENUGREEK ON THE FRESHWATER PRAWN MACROBRACHIUM ROSENBERGII - R. POONGODI; P. SARAVANA BHAVAN; T. MURALISANKAR; S. RADHAKRISHNAN (International Journal of Pharma and Bio Sciences, 2012)
A 60 day feeding trial was conducted to determine the growth performance of Macrobrachium rosenbergii post larvae (PL) on Allium sativum (Garlic), Zingiber officinale (Ginger), Curcuma longa (Turmeric) and Trigonella foenum-graecum (Fenugreek) incorporated diets. Survival rate (SR) ranged from 69.0-80.0% in experimental diets fed PL groups were recorded against 66.0% in control. The elevation in SR was in the order of garlic > ginger > turmeric > fenugreek. Similar trend in elevation of FR was recorded, which in turn increases the WG in experimental PL over control. The same patterns of improvements were observed in SGR, FCE, PCE, ME and GE. Concurrently, the values obtained for CF and FCR were in decreasing pattern (garlic < ginger < turmeric < fenugreek). This indicated the fact that the experimental feeds were superior in quality than that of control. Concentrations of total protein, amino acid, RNA, DNA, RNA/DNA and carbohydrate as well were found to be elevated in experimental diets fed PL when compared with control. Instead, herbal dependent utilization of lipid was noted in PL, and thus, the elevation of total lipid was recorded in just the reverse order, garlic < ginger < turmeric < fenugreek. All the data were significant at P<0.05. The herbal growth promoter induced transcription rate, which in turn increased RNA and total amino acid, which ultimately enhances proteins synthesis in M. rosenbergii PL. This ability was higher with garlic included feed followed by ginger, turmeric and fenugreek. Therefore, these herbs could be taken as supplementary materials in aqua feed formulation.